Implementasi Protokol Universal Plug and Play (UPnP) pada Sensor dan Aktuator untuk Otomasi Lampu - Muhammad Mahar Jahary; Mochammad Hannats Hanafi Ichsan; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The use of wireless network technology is very popular, especially for use in smart homes. The amount of technology contained in the home provides an increase in the quality of human life because it provides efficiency in carrying out activities. However, the disadvantage of many technologies is the use that still uses a lot of control to run the technology. To be able to correct this problem, this study developed the use of Universal Plug and Play protocol (UPnP) to connect from various device technologies to one control. UPnP can run with various programming languages ​​and can communicate automatically by utilizing discovery and description functions. The researcher made the first two smart home devices using a raspberry pi device for the center of the system on the device and used the PIR sensor as input value from the captured infrared intensity while for the actuator using the lamp. then the second device uses raspberry pi as a performance center and LDR sensor to capture the light emission. Control points as users also use raspberry pi can be searched, found and requested for any services contained in the smart home device. Once recognized, the user can request status from the current condition of the device or send an order to turn on or turn off the light. The results of the study to test the response time performance between control points and one smart home device obtained an average of 293.32 milliseconds for the first time, averaging 169.76 milliseconds for response time after first being recognized and an average of 726 milliseconds for time the control point response is connected to two smart home devices for the first time.